A Quality Improvement Approach to Influence Value-based Mucolytic Use in the PICU. Issue 4 (July 2021) - Gillis, Holly Catherine; Dolan, Kevin; Sargel, Cheryl L.; Thompson, R. Zachary; Lutmer, Jeffrey E.
Abstract : Introduction: High-cost medication administration, despite lacking evidence for use, results in poor healthcare value. This work aimed to reduce dornase-alfa utilization in critically ill mechanically ventilated children. Methods: The project employed an observational pre-post design to develop a value-based clinical pathway to guide provider choice in mucolytic utilization in a quaternary pediatric intensive care unit. This pathway was designed to continue using low-cost mucolytic aerosols (hypertonic saline, N-acetylcysteine) but decrease new starts and total doses per 100 patient days (P100PD) dornase-alfa among patients for whom there is little to no supporting evidence. Interventions included a departmental journal club for fellow and attending physicians and a rolling introduction of the pathway to residents and respiratory therapists. Control charts serially tracked ordering changes and location-specific dornase alfa orders. Results: New dornase-alfa starts P100PD decreased by 53% (1.17–0.55), and total doses P100PD decreased by 75% (16–4). N-acetylcysteine ordering more than doubled; however, total doses of P100PD remained unchanged after the intervention. The use of 3% sodium chloride increased significantly from 0.28 to 4.15 new starts and 4.37 to 38.84 total doses P100PD. Mechanical ventilation days P100PD decreased, suggesting there were no measured adverse effects of pathway implementation. The reduction in dornase-alfa utilization resulted in a cumulative and sustained 59% mucolytic cost reduction ($2183.08–$885.77 P100PD). Conclusion: A clinical pathway prioritizing pharmacoeconomics when evidence for use is lacking can improve health care value without adversely affecting patient outcomes.